When best friendships end: young adolescents' responses to hypothetical best friendship dissolution and associations with real-life friendship outcomes - Bowker, Julie C.; Weingarten, Jenna P.; Etkin, Rebecca G.; Dirks, Melanie A. (Frontiers in Developmental Psychology, 2024)
This study examined young adolescents' responses to two types of hypothetical best friendship dissolution (complete and downgrade dissolutions). Responses included their attributions, emotional reactions, and coping strategies. It also considered whether responses vary across dissolution type and are related to the real-life friendship-specific outcomes of best friendship dissolution and friendship quantity. Data were collected from 318 young adolescents at two time points (Time 1 (T1): Mage = 11.87 years) and included a newly-developed vignette measure of responses to hypothetical complete and downgrade dissolutions (T1), real-life complete and downgrade dissolutions experienced by participants (T2), and friendship (T1, T2). Findings showed that adolescents responded differently in their emotional reactions and coping strategies to hypothetical complete and downgrade dissolutions.Path models revealed unique linkages between several responses, such as vengeful coping and the reallife friendship-specific outcomes. Findings suggest variability in how young adolescents respond to hypothetical best friendship dissolutions and that such variability may explain differences in their reallife friendships.